Effects of biologically-active preparation on physical and chemical parameters of minced meat - Zamzagul Moldakhmetova; Aigul Tayeva; Gulnara Shambulova; Gaukhar Kuzembayeva; Madina Kozhakhiyeva; Altyn Kapbassova; Nursulu Akhmetova; Gulbagi Orymbetova (Caspian Journal of Environmental Sciences)
The introduction of biologically-active preparations (BAP) in Konskaya Varenaya (Horse and cooked sausage) significantly alters the functional processing and structural-mechanical properties of minced meat, thereby affecting the quality of the final product. This study aimed to determine the optimal formulation of combined cooked sausage with BAP by examining the influence of varying amounts of the preparation on minced meat and sausage quality. Key functional and processing characteristics, including water-binding power (WBP), moisture content, pH level, yield, and water activity, as well as structural-mechanical properties such as yield value, adhesiveness, and plasticity, were assessed using standard laboratory methods. The results indicated that WBP is significantly influenced by both the quantity of BAP and cutting time. Additionally, the inclusion of egg-derived BAP positively affected the protein system of minced meat, leading to an increased pH and enhanced WBP.